Insect Resistance Transgenic Crops and their Current Status in India - Priyanka, N.; Rajashekhar, M.; Bharghavi, K.; Akhil, G.; Asritha, CH.; Keerthana, B.; Sruthi, K. (Chronicle of Bioresource Management, 2020)
As the world’s population rises, so does the need for food, which current breeding methods can only partially provide. However, new biotechnological advancements like gene editing and transgenic crops enable plants to produce more and have higher nutritional value. The Indian government approved Bt cotton as the first transgenic crop to be produced commercially in March 2002. However, worries about possible human toxicity and allergenicity, potential environmental risks like gene flow, detrimental impacts on non-target organisms, and resistance development in weeds and insects hinder the widespread acceptance of transgenic crops harboring foreign genes. Moreover, before releasing of any GM or transgenic crop there is great need to conserve the germplasm of the crops in national and international germplasm repositories.